Lower Bone Mineral Density in Patients with Parkinson’s Disease: A Cross-Sectional Study from Chinese Mainland - Gao, Huimin; Wei, Xiaobo; Liao, Jinchi; Wang, Rui; Xu, Jiehua; Liu, Xu; Pan, Xiaoping; Li, Ze; Li, Zhong; Xia, Ying; Wang, Qing (Frontiers in Aging Neuroscience, 2015)
Objectives Although several lines of evidence have suggested that patients with Parkinson’s disease (PD) have a higher risk of osteoporosis and fracture, the association between bone mineral density and severity of PD patients is unknown. Methods We performed a cross-sectional study of 54 patients with PD and 59 healthy age-matched controls. Multiple clinical scales were used to evaluate the severity of PD, and serum levels of calcium, phosphorus, and homocysteine were measured to determine bone mineral density’s association with PD severity. Results BMD in PD patients was significantly lower than in healthy controls. The BMD scores of the spine, femoral neck, and hip were lower in females than in males in the healthy group. In the PD group, BMD in the hip was significantly lower in females compared to males. There was a negative correlation between daily L-dopa dosage and BMD in the spine and hip in the PD group, while BMD in the spine, neck, and hip was significantly correlated with severity of PD. Besides, we found that among the lumbar spine, femoral neck and hip, bone loss in the lumbar spine was the most severe in PD patients based on the T-scores. Conclusions Our findings support the hypothesis that patients with PD have a higher risk of osteoporosis, and that low BMD in the spine, femoral neck, and hip may indirectly reflect the severity of PD. Our findings have prompted us to pay more attention to osteoporosis in the lumbar spine in Chinese PD patients.